-5(-2x+3)-1=8+15x

Simple and best practice solution for -5(-2x+3)-1=8+15x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-2x+3)-1=8+15x equation:


Simplifying
-5(-2x + 3) + -1 = 8 + 15x

Reorder the terms:
-5(3 + -2x) + -1 = 8 + 15x
(3 * -5 + -2x * -5) + -1 = 8 + 15x
(-15 + 10x) + -1 = 8 + 15x

Reorder the terms:
-15 + -1 + 10x = 8 + 15x

Combine like terms: -15 + -1 = -16
-16 + 10x = 8 + 15x

Solving
-16 + 10x = 8 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-16 + 10x + -15x = 8 + 15x + -15x

Combine like terms: 10x + -15x = -5x
-16 + -5x = 8 + 15x + -15x

Combine like terms: 15x + -15x = 0
-16 + -5x = 8 + 0
-16 + -5x = 8

Add '16' to each side of the equation.
-16 + 16 + -5x = 8 + 16

Combine like terms: -16 + 16 = 0
0 + -5x = 8 + 16
-5x = 8 + 16

Combine like terms: 8 + 16 = 24
-5x = 24

Divide each side by '-5'.
x = -4.8

Simplifying
x = -4.8

See similar equations:

| 19x-5x=168 | | 1/2y=6/1 | | 5g=3g+10 | | a^29=5 | | 16=4V-8 | | x^2-8x+y^2-8y=4 | | whatisx-27=62forx | | x^2+ax+3=0 | | N^2+10n=16 | | 3-19=9x-2-8x | | 24x-12y=25 | | 15=5(m-7) | | y=(3+2k)x | | 2x+22=10-74 | | -10=-14a+14a | | 3+x-11=3 | | 9+2(y-3)=12 | | (35+3x+9y)-(5x+7y+27)=0 | | -2x+12=2x | | 4y^2-y+y^2= | | 6-5c=-28 | | T=6s+21.75 | | 8+2ln(x)=3 | | 6x+8=2x^2 | | f(x)=5x(x^2-2x-1) | | Fx+gx=j | | (18+5x+8y)-(2x+9y+40)=0 | | x-(7)=13 | | 2x-7y-10=0 | | =2(a+3)+3(2a-1) | | 1.5(x-6)=-6 | | 2h=-12 |

Equations solver categories